Language Assessment for School-aged Children: Examining the Evidence and Describing Clinical Practice - Denman, Deborah Ann (Curtin University, 2019)
Accurate speech-language pathology assessment is vital for determining the intervention needs of children with language disorders. This thesis investigated research evidence in relation to language assessment practices for school-aged children. Consensus on terminology for describing assessments was obtained and current language assessment practices were examined to identify actions to help improve speech-language pathologist’s implementation of evidence-based practice recommendations. Information gained from this thesis will assist with enhancing service provision for school-aged children with language disorders.